The Barriers of Florida’s Anti-LGBTQ+ Laws in Healthcare and Its Impact on the Mental Health of Gender and Sexual Minorities - Xuban Palau Villarreal; Daisy Valle; Raja Al-Bahou; Stephanie F. Ryan (Journal of Psychosexual Health)
Introduction: Recent legislation in Florida, including SB 254, SB 1580, and HB 1557/1069, has created barriers for LGBTQ+ individuals, particularly those seeking gender-affirming care (GAC). SB 254 limits access to GAC by restricting Medicaid coverage and allowing only physicians to provide treatment. SB 1580 permits healthcare providers to refuse treatment based on personal beliefs, further reducing access. HB 1557/1069 prohibits discussions of gender identity and sexual orientation in schools, increasing social stigmatization of LGBTQ+ individuals. These legal changes contribute to worsening mental health outcomes in this community, notably depression and anxiety. Methods: A prospective survey of 131 LGBTQ+ individuals and allies in Florida was conducted using convenience sampling at local LGBTQ+ events. The survey assessed the perceived impact of each law on daily life, access to healthcare, and mental health. Depression and anxiety were measured using the PHQ-9 and GAD-7 scales. Results: Transgender and non-binary participants were disproportionately impacted by SB 254, with 85% reporting reduced access to GAC. These participants also reported longer delays in receiving care and heightened fears of future healthcare refusals due to SB 1580. LGBTQ+ participants reported noted increased anxiety due to the broader stigmatizing effects of HB 1557/1069 in educational and social settings. Among gender minorities, 82% reported severe depression. Conclusion: Gender minorities in Florida face severe consequences from recent legislation, including significant barriers to gender-affirming healthcare and heightened mental health challenges. This study showed a disproportionate impact on gender minorities which prompts targeted advocacy and healthcare reforms to support this vulnerable population.